T-Cell Immunity Panel Measures CMV-Specific CD4 and CD8 T-Cell Responses. (4th October 2017) - Lutgen, Cory B; Flebbe-Rehwaldt, Linda; Kleiboeker, Steve; Fausett, Stephanie; Cordes, Chrissy; Rodgers, Jessica; Steffens, Kathie; Altrich, Michelle
Abstract: Background: Infection and disease from human cytomegalovirus (CMV) is a major complicating factor for both solid organ and hematopoietic stem cell transplant recipients. Antiviral therapy is often used to control CMV infections, but presents problems of toxicity, antiviral resistance and excessive costs. Currently, treating physicians are limited in the information and data available to assess a patient's ability to control a potential CMV infection post-transplant. Recent studies have shown that measuring a patient's CMV specific T cell mediated immunity may provide valuable information to physicians for monitoring CMV infection/disease in transplant patients and may aid in determining which patients need antiviral therapy. Methods: For this purpose, a flow cytometry assay was developed to determine the percentages of CD4+ and CD8+ T cells that respond to stimulation with CMV antigen. Assessment of CMV specific response is based upon the cellular activation surface marker CD69 in conjunction with IFNg, TNFα, and IL-2 cytokine production. Three CMV antigens were used to assess patient immunity; a whole viral lysate, a peptide pool of pp65, and a peptide pool of IE-1. Results: Our data indicate that CD8 T cells respond primarily to the pp65 and/or IE-1 peptide pools while the CD4 T cells respond primarily to the viral lysate. Detection of both CD4 and CD8 responding populations at levels above background, ≥ 0.2% of the parent population, indicates that a patient's immune system has previously been exposed to CMV. Validation of 23 CMV seropositive samples demonstrated immune responses for all 23 samples above 0.2% for at least one of the three intra-cellular cytokines and at least one of the three CMV antigens. Validation of five CMV seronegative samples demonstrated immune responses below 0.2% (when excluding underlying, unrelated immune responses). Included for each sample is a positive (Staphylococcal Enterotoxin type B) control to assess patient's overall ability to mount an immune response and negative (media) control to capture the presence of an underlying immune response. Conclusion: This assay evaluates a patient's pre-existing CMV specific T cell immunity and their global T cell function. Disclosures: C. B. Lutgen, Viracor Eurofins Clinical Diagnostics: Employee, Salary; L. Flebbe-Rehwaldt, Viracor Eurofins Clinical Diagnostics: Employee, Salary; S. Kleiboeker, Viracor Eurofins Laboratories: Employee, Salary; S. Fausett, Viracor Eurofins Clinical Diagnostics: Employee, Salary; C. Cordes, Viracor Eurofins Clinical Diagnostics: Employee, Salary; J. Rodgers, Viracor Eurofins Clinical Diagnostics: Employee, Salary; K. Steffens, Viracor Eurofins Clinical Diagnostics: Employee, Salary; M. Altrich, Viracor Eurofins Laboratories: Employee, Salary